Pengaruh Nilai Tukar Rupiah Terhadap Indeks Saham Syariah Indonesia Periode 2018-2020 - Al Bara Al Bara (AGHNIYA : Jurnal Ekonomi Islam, 2021)
The purpose of this study was to determine the relationship between the rupiah exchange rate and the Islamic stock index. The research approach taken is a quantitative approach. The data source comes from secondary data. The data collection technique is done by documenting or retrieving data online from the official state website. Based on the research conducted, the conclusion is that the rupiah exchange rate has a positive relationship to the Indonesian Islamic stock index, because the rupiah exchange rate has an effect on Islamic stock prices, this can be seen from the t test which says T count is 6.5097, T table is equal to 2,0017. 6,509 2,0017 then H0 is rejected and Ha is accepted, which means that the exchange rate variable has a significant effect on the ISSI. Therefore this study raises the rupiah exchange rate and the Indonesian Islamic stock index with the intention to determine the effect and significance of the rupiah exchange rate on the Index Sharia Shares of Indonesia during the 2018-2020 period. The relationship between the exchange rate of 56.8% and the share price of Indonesian Islamic stocks is the remaining 43.2% which is not influenced by other variables, so that the variables examined between the rupiah exchange rate and Indonesian Islamic stocks have an effect because the percentage exceeds 50%. It can be concluded that the rupiah exchange rate affects the Indonesian Islamic stock index